Examining Gender Differences in Aggression as a Predictor of Anxiety, Depression, and Suicide in a Cross‐Sectional French Sample - Sylvia Martin (Health Science Reports)
ABSTRACT Background and Aims The expected outcomes of the Covid‐19 pandemic have a supposedly worsened impact on mental health and suicidal risk. Traditionally, males were supposed to have heightened Aggression and impulsivity in stressful times. We aim to measure the actual differences that existed during the COVID‐19 pandemic across male and female participants. Methods An overall number of 288 females/95 males (mean age: men = 34.97; women = 32.90 years) participants were recruited. The protocol included questionnaires about suicidal risk, anxiety, depression, impulsivity, aggression, hopelessness, and demographics. Results Differences exist in the sense of loneliness, the number of persons being isolated with, anxiety, and several impulsivity subdimensions. A correlation existed for both men and women for anxiety and depression, revealing the impact of aggression. Suicide men's scores correlated with anxiety and depression, lack of premeditation, and hopelessness. Women also had such correlation, except for lack of perseverance, social dimensions, and aggression. Analyses reveal the predictive impact of hopelessness and aggression on anxiety, depression, and suicidal risk predominantly in females. Conclusion Our results contradict common ideas that men have heightened aggression and impulsivity. Further research needs to address aggression issues.